1996
DOI: 10.1093/infdis/174.supplement_2.s240
|View full text |Cite
|
Sign up to set email alerts
|

Focused Peer-Mediated Educational Programs Among Female Sex Workers To Reduce Sexually Transmitted Disease And Human Immunodeficiency Virus Transmission In Kenya And Zimbabwe

Abstract: Peer-mediated education programs in Kenya and Zimbabwe focusing on female sex workers for the control of human immunodeficiency virus (HIV) infection and other sexually transmitted diseases (STDs) have led to increased condom use and increased adoption of other safer sex practices, as well as declines in STD and HIV incidence among female sex workers. It is likely that similar declines have occurred among their clients and possibly in the general community, although supporting data are limited. These results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 11 publications
2
79
0
Order By: Relevance
“…These assets might form a starting point for projects aiming to achieve greater assertiveness and confidence amongst sex workers in relation to their sexual health, even within the poverty and violence of their working and living conditions. There have already been some successes in promoting condom use and reducing levels of sexually transmitted disease in equally disadvantaged communities of women in Zimbabwe, Mocambique, Malawi and Zambia (Dube and Wilson, 1996;Ngugi et al, 1996;Wilson, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These assets might form a starting point for projects aiming to achieve greater assertiveness and confidence amongst sex workers in relation to their sexual health, even within the poverty and violence of their working and living conditions. There have already been some successes in promoting condom use and reducing levels of sexually transmitted disease in equally disadvantaged communities of women in Zimbabwe, Mocambique, Malawi and Zambia (Dube and Wilson, 1996;Ngugi et al, 1996;Wilson, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Such grassroots involvement aims to increase peoples' sense of healthrelated empowerment or self-efficacy through transferring responsibility for health promotion from the hands of outside 'experts' into the hands of lay community members. Furthermore, the peer education approach provides a backdrop for members of vulnerable communities to debate and negotiate healthier patterns of behaviour at the collective level, aiming for a reformulation of group norms of sexual and health-seeking behaviour -rather than seeking to persuade individuals to make rational decisions to change their behaviour (as traditional information-based 5 health education sought to do) (Campbell, 1998;Dube and Wilson, 1997;Ngugi et al, 1996).…”
Section: The Mothusimpilo Projectmentioning
confidence: 99%
“…Tropical Medicine and International Health volume 13 no 5 pp 659-679 may 2008 (Ngugi et al 1988(Ngugi et al , 1996 Longitudinal India, Calcutta Das et al 1994;Jana et al 1994Jana et al , 1998Jana et al , 2004Pal et al 1994;Jana & Singh 1995) prevalences of over 50% reported from similar settings elsewhere in India. A three-to fivefold reduction in prevalent STIs was documented Das et al 1994;Jana et al 1994Jana et al , 1998Jana et al , 2004Pal et al 1994;Jana & Singh 1995).…”
Section: Structural Interventionsmentioning
confidence: 99%
“…In Zaire (Laga et al 1994) and Nairobi (Ngugi et al 1988(Ngugi et al , 1996 they examined the effect on incident HIV while in Peru (Sanchez et al 2003) and China (Ma et al 2002) the primary outcome was incident STIs. Only the Chinese cohort reported the loss to follow-up, which was 50%.…”
Section: Treatment Of Bacterial Sexually Transmitted Infections Combimentioning
confidence: 99%
“…Peer workers have been shown to be most effective in catalysing change in their communities, from condom use to clinic attendance to structural changes. 24 Related and important concepts are structural interventions and creating an enabling environment. Structural interventions address root causes of problems, such as the difficulties of individual sex workers to negotiate condom use.…”
Section: Targeting High-risk Populationsmentioning
confidence: 99%